Children’s understandings of well-being. Towards a child standpoint - Casas Aznar, Ferran (Sociedad e Infancias, 2020)
Fattore, T., Mason, J. with Watson, E. (2016). Children’s understandings of well-being. Towards a child standpoint. Dordrecht: Springer, 280 páginas. ISBN: 978-94-024-0827-0.